Fitofagia do predador Podisus nigrispinus (Dallas, 1851) (Hemiptera: Pentatomidae) em diferentes brassicáceas - Grigolli, J. F.J. (2017)
The purpose of this study was to investigate the development and reproduction of the zoophytophagous predator Podisus nigrispinus (Dallas) (Heteroptera: Pentatomidae) fed kale, broccoli and cabbage affects its. Nymphs and adults of this predator were fed on larvae of Plutella xylostella (L.) (Lepidoptera: Plutellidae) as prey with kale, cabbage, or broccoli. In the nymph period, the duration and prey consumption were similar with all the Brassicacea cultivar. However, nymph viability was higher for predators with broccoli leaves. The mean weight of 5th-instar nymphs, newly emerged females and the sex ratio were similar among the Brassicacea cultivars, while newly emerged males were heavier with kale and broccoli leaves. The supply of broccoli leaves resulted in greater oviposition, higher number of eggs per egg mass and longer longevity of P. nigrispinus males and females. Furthermore, the consumption of P. xylostella larvae by adult predators was higher with these cultivars. The net reproductive rate (R0) and mean generation time (T) were highest for predators with prey and broccoli leaves. The reproductive parameters of P. nigrispinus were enhanced when fed on P. xylostella larvae with and broccoli leaves, which can be an alternative diet in laboratory rearing of this predator.